Red emission from InGaN active layer grown on nanoscale InGaN pseudosubstrates. (16th February 2023) - Cai, Wentao; Wang, Jia; Park, Jeong-Hwan; Furusawa, Yuta; Cheong, Heajeong; Nitta, Shugo; Honda, Yoshio; Pristovsek, Markus; Amano, Hiroshi
Abstract: We demonstrated nanoplatelet In x Ga1− x N pseudosubstrates with In content varying from 0 to 0.3 on low-dislocation-density GaN substrates. These nanoplatelets efficiently relax in-plane strain, thus allowing for the use of a thick active layer to reduce built-in polarization. The 15 nm thick InGaN active layers grown under the same conditions on these nanoplatelets showed a remarkable cathodoluminescence redshift from 460 to 617 nm, suggesting enhanced In incorporation efficiency in InGaN nanoplatelets with higher In content. Moreover, the 617 nm-emitting sample presented an imperceptible blueshift under excitation-power-dependent photoluminescence, indicating a weak polarization field introduced by the high-In-content pseudosubstrates and the thick active layer.